Shear-force exfoliation of indium and gallium chalcogenides for selective gas sensing applications - Marvan, Petr; Mazánek, Vlastimil; Sofer, Zdeněk (Nanoscale, 2019)
Layered chalcogenides AIIIBVI of gallium and indium form a group of semiconducting nanomaterials with huge potential in electronic, sensor and energy storage applications. However, the preparation method predetermines the usage of the prepared nanomaterial. In this paper, we investigated shear-force milling exfoliation in a surfactant free water/ethanol mixture on indium and gallium chalcogenides and their utilization in the gas sensing of volatile organic compounds (VOCs). The exfoliation of bulk materials in a surfactant-free environment helped to avoid any surface contamination and allowed the preparation of materials without non-covalently bonded large organic molecules. Furthermore, the gas-sensing properties were evaluated by electrical impedance spectroscopy on VOCs. Our results showed high sensitivity and selectivity towards methanol. This suggests that shear-force milling is an effective method for the exfoliation of indium and gallium chalcogenides which can find application in the selective gas sensing of VOCs.